Characterization of black phosphorous synthesized via ball-milling technique for the effect of milling media and time - Mohd Suan, Mohd Shahadan; Lukman, Zainul Abidin; Nurdin, Irwan (Penerbit Akademia Baru, 2024)
Black phosphorus (BP), a unique arm-chair structure 2D material named for its distinctive black colour has been known to have intriguing properties include high energy storage and energy band-gap capabilities. BP is synthesized from the red phosphorus by using the ball-milling technique as an alternative to the existing complicated method which involves hazardous white phosphorus, high-temperature, and high-pressure conditions. Hence, we investigated and compared the effects of using alumina, stainless steel, and agate media on BP's physical and structural properties. The effects of milling time were performed afterward by using stainless-steel media for 1 h to 5 h. The ball-milling process at 450 rpm for 5 h in stainless steel media has transformed the coarse red powder into a dark black colour fine powder. The XRD analysis on the as-prepared powder revealed the existence of pure and crystalline black phosphorus. The Raman analysis indicated the apparent existence of BP structure synthesized. Observation of the FESEM images showed the BP existed with nanosized and flaky-shaped microstructure.